The Garrick Papers: Provenance, Publication, and Reception. (16th September 2020) - Smith, Nicholas
Abstract: The Garrick Papers are among the brightest literary jewels in the Forster Collection at the Victoria and Albert Museum. This article reconstructs their provenance, along with that of significant deposits of Garrick's correspondence held elsewhere, and examines the circumstances that led to their publication in 1831–1832. It uses unpublished manuscripts, Chancery records, and annotated sale catalogues to identify the chain of ownership between 1822, when the executors of Eva Maria Garrick (1724–1822), the actor's widow, found them in two cabinets at her Thames-side villa at Hampton, and 1876, when they were bequeathed to the South Kensington Museum. It reveals the original order of Garrick's epistolary archive, and his and others' involvement in its appraisal and arrangement, the various depredations and augmentations that occurred during the fifty years that followed Eva Maria Garrick's death, and the early critical reception and publishing history of the printed editions of Garrick's correspondence.